(untitled) (The Journal of Psychology and Sociology, 2019)
The study of the psychology of money and work with young people on the formation of monetary culture is especially important now in Kazakhstan for the formation of independence, financial intelligence, economic freedom, the ability to make adequate and competent decisions, as well as the full growth and development of a young, promising in all respects the personality of a citizen of his country. In this article the psychological analysis of the main factors influencing the relation of the person to money as not only the healthy relation to monetary values, but also all value and semantic aspects of the relations of the person to itself and to the world, including culture of behavior as a whole depends on them is considered. Value-semantic attitude to money is formed during the formation and development of man, that is, throughout his life. When analyzing the factors of external and internal influence on the human attitude to money, the fact that modern money has long gone beyond the economic regulator of social relations, becoming a very important aspect, exposing the psychological problems of the individual and society to the maximum limit, was taken into account. Adrian Fernham in his work "Personality and money" identified six main factors that directly affect the monetary behavior of a person, including his social status, environment and economic status, gender of the individual, his age and personal characteristics. Each of these factors has been discussed in detail in our article, thanks to the analysis of modern research carried out taking into account the factor structure of the relationship to money. In General, getting rid of ideological myths and equalizing ethics of the socialist period of the history of Kazakhstan, mastering new strategies of coping behavior will allow in the future to form a healthy attitude to money, their social functions, will lead to the modern level of development of monetary relations. Formed a healthy attitude to money will allow young people to move away from consumer attitudes and destructive-passive expectations of help from family, friends and the state. Key words: money, value, external and internal factors, culture, attitude.